The SWOT Analysis: Islamic Branding Strategy at XYZ Islamic Hospital Bekasi - Rian Pranata Pran; Henny Hanna (Siber Journal of Advanced Multidisciplinary, 2026)
Abstract: Islamic branding in hospitals has become an important strategy in increasing patient trust and visits in the era of increasingly tight competition in healthcare services. The purpose of this study is to analyze the Islamic brand strategy at XYZ Islamic Hospital Bekasi using the SWOT (Strengths, Weaknesses, Opportunities, Threats) method. The analysis results show that the Islamic brand has strengths in building a positive image and service differentiation, but still faces challenges in the form of limited facilities, human resources, and competition from both modern hospitals and other Islamic hospitals. The recommended strategies are strengthening professional Islamic branding, improving service quality, and optimizing digitalization and community-based promotion.   Keyword: SWOT, Islamic Branding, Hospital, Strategy, Islamic Brand